Effect of Free Radical Scavenger (Tempol) on Intrarenal Oxygenation in Hypertensive Rats as Evaluated by BOLD MRI - Li, Lu-Ping (2005)
PURPOSE: To demonstrate a differential response following administration of a free radical scavenger, tempol, in kidneys of hypertensive compared to normotensive rats. MATERIAL AND METHODS: Data were obtained in spontaneously hypertensive rats (SHR, N = 5). Wistar-Kyoto rats (WKY, N = 6) were used as normotensive controls. RESULTS: Consistent with prior reports, SHRs show a significant response to tempol (R(2)*decreased from 40.56 ± 0.66 second(−1) to 28.58 ± 0.6 second(−1) in medulla, P < 0.05), while WKY rats exhibit a minimal change (R(2)* measuring 22.36 ± 4.38 second(−1) pre-tempol and 21.57 ± 4.78 second(−1) post-tempol, in medulla). The post-tempol R(2)* in SHR was found to be comparable to pre-tempol values in WKY rats, suggesting an improved medullary oxygenation in SHRs. CONCLUSION: Based on both baseline R(2)* values and the differential effect of the free radical scavenger on renal medullary oxygenation, BOLD MRI can distinguish hypertensive from normal kidney in rats.